PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS NEGOSIASI PADA SISWA KELAS X SMK PLUS FATAHILLAH GEGESIK TAHUN AJARAN 2024/2025 - Nisa, Khoerotun; Efendi, Irfan; Masrurih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the activity of the application of the Problem Based Learning (PBL) model in learning to write negotiation texts and to determine the effectiveness of the application of the Problem Based Learning (PBL) model in learning to write negotiation texts for class X students of SMK Plus Fatahillah Gegesik in the 2024/2025 Academic Year. This study uses an experimental method with research subjects, namely 28 class X TKR 2 students as the control class and 28 class X TKJ students as the experimental class. The instruments used in this study are observation and test data. The results of this study show an increase in student learning outcomes based on the results of observations of teacher activities obtaining a score of 3.6 with a very good category and the results of observations of student activities obtaining a score of 2.8 with a good category. It is proven that the Problem Based Learning model can increase student activity. Based on the results of statistical calculations using the independent samples t-test, the t count was 3.334 and the t table was 2.007. So t count 3.334>2.007, this shows that H0 is rejected and H1 is accepted. It is proven that the Problem Based Learning (PBL) model is effective in learning to write negotiation texts in class X of SMK Plus Fatahillah Gegesik.